Tension band wiring in a rare case of isolated acromion fracture: a case report - Jain, Prateek; Atram, Vikas; Mittal, Ayush; Arora, Chandan (International Journal of Research in Orthopaedics, 2022)
Fracture of the acromion process is an uncommon injury. The most common mechanism of injury is direct trauma to the acromion. Isolated acromion fractures are rare as usually they are associated with concomitant skeletal and soft tissue injuries of the shoulder. We present a case of a 45-year-old male with a type 3 fracture of acromion process with reduction of subacromial space. Patient was managed surgically and fracture was fixed using tension band wiring. Patient was followed up using UCLA, DASH and VAS scores and showed good radiological and functional outcomes. Minimally displaced fractures should be regularly followed up for displacement and sub-acromial space compromise. Although acromion fractures are usually treated conservatively, albeit a higher non-union rate, they should be treated surgically in the event of displacement or sub-acromial space reduction, in order to achieve good functional recovery.